2017
DOI: 10.1002/mc.22678
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between calcium intake and polymorphisms in genes essential for calcium reabsorption and risk of colorectal neoplasia in a two‐phase study

Abstract: The SLC8A1 (solute carrier family 8, member 1) gene, encoding Na+/Ca2+ exchanger, is essential in regulating calcium reabsorption and homeostasis. Calcium homeostasis plays a key role in cell proliferation and apoptosis. We hypothesized that polymorphisms in five calcium-regulating genes (SLC8A1, ATP2B1, CALB1, CALB2, and CABP1) interact with calcium intake in relation to the risk of colorectal neoplasia. A two-phase (discovery and replication) study was conducted within the Tennessee Colorectal Polyp Study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…miR‐515, miR‐577, and miR‐383 all silenced these six pivotal genes separately when they were highly expressed. DLGAP5 is associated with the development of a variety of tumors, such as ovarian cancer, breast cancer, and NSCLC, due to its ability to inhibit mitosis and block cell cycle progression . Calcium is one of the key factors in stabilizing the cell cycle, and CALB1 can interfere with the resorption and homeostatic processes of calcium, ultimately regulating cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐515, miR‐577, and miR‐383 all silenced these six pivotal genes separately when they were highly expressed. DLGAP5 is associated with the development of a variety of tumors, such as ovarian cancer, breast cancer, and NSCLC, due to its ability to inhibit mitosis and block cell cycle progression . Calcium is one of the key factors in stabilizing the cell cycle, and CALB1 can interfere with the resorption and homeostatic processes of calcium, ultimately regulating cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…DLGAP5 is associated with the development of a variety of tumors, such as ovarian cancer, breast cancer, and NSCLC, due to its ability to inhibit mitosis and block cell cycle progression. 57,58 Calcium is one of the key factors in stabilizing the cell cycle, and CALB1 can interfere with the resorption and homeostatic processes of calcium, ultimately regulating cell apoptosis. 59 In addition, studies have shown that CALB1 can play a role in early tumor diagnosis and recurrence prediction.…”
mentioning
confidence: 99%
“…However, CABP1 has rarely been studied in the field of oncology. Certain studies have demonstrated that aberrant CABP1 expression was associated with adenoma risk, particularly for multiple/advanced adenomas (44,48,49). In addition, Zhang et al (50) previously reported that CABP1 is upregulated in glioblastoma tissues compared with normal brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS analysis demonstrated that variants of SLC8A1 were closely related to the risk of colorectal neoplasia and calcium intake and inversely correlated with colorectal adenomas (Zhao et al, 2017a). SLC8A1 functions as a Na + /Ca 2+ exchanger and mediates the extrusion of Ca 2+ ion across the cell membrane (Khananshvili, 2013).…”
Section: Slcs In Human Diseasesmentioning
confidence: 99%